(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2015)
The implementation of shariah criminal law in Malaysia, like any other laws; necessitate the legal enforcers to be knowledgeable about the laws and the ways how the laws are applied. However, the enforcement and prosecution of shariah criminal law in Malaysia are facing the problem where the legal enforcers are from mix backgrounds as far as their knowledge is concerned; some of them are of legal background, while others are from non legal background. This is more apparent from amongst the legal enforcers from the religious enforcement unit where their appointment does not condition the need to have a legal background. This has caused a mere understanding of the provisions in the acts and enactments and most of the time, it contributes to misunderstanding in interpreting the laws. After so many critics made due to the failure that occurred in carrying out the operations in enforcing the Shariah criminal law, the formation of sets of guidelines is viewed as a way to solve the problem relating to the misunderstanding among the legal enforcers. This is because, one of the characteristics of the guidelines is that the elaboration is structured so to enable understanding even if it is read by the public. Keywords: guidelines, ethics, enforcement, prosecution, syariah offences